Comparing and Predicting the Costs and Outcomes of Patients with Major and Minor Stroke Using the Boston Acute Stroke Imaging Scale Neuroimaging Classification System - Cipriano, L.E.; Steinberg, M.L.; Gazelle, G.S.; González, R.G. (American Journal of Neuroradiology, 2009)
BACKGROUND AND PURPOSE: A neuroimaging-based ischemic stroke classification system that predicts costs and outcomes would be useful for clinical prognostication and hospital resource planning. The Boston Acute Stroke Imaging Scale (BASIS), a neuroimaging-based ischemic stroke classification system, was tested to determine whether it was able to predict the costs and clinical outcomes of patients with stroke at an urban academic medical center.MATERIALS AND METHODS: Patients with ischemic stroke who presented in the emergency department in 2000 (230 patients) and 2005 (250 patients) were classified by using BASIS as having either a major or minor stroke. Compared outcomes included death, length of hospitalization, discharge disposition, use of imaging and intensive care unit (ICU) resources, and total in-hospital cost. Continuous variables were compared by univariate analysis by using the Student t test or the Satterthwaite test adjusted for unequal variances. Categoric variables were tested with the χ2 test. Multiple regression analyses related total hospital cost (dependent variable) to stroke severity (major versus minor), sex, age, presence of comorbidities, and death during hospitalization. Logistic regression analysis was applied to identify the significant predictive variables indicating a greater likelihood of discharge home.RESULTS: In both years, individuals with strokes classified as major had a significantly longer length of stay, spent more days in the ICU, and had a higher cost of hospitalization than patients with minor strokes (all outcomes, P < .0001). All deaths (8 in 2000, 26 in 2005) occurred in patients with major stroke. Whereas 73% of patients with minor stroke were discharged home, only 12.2% of patients with major stroke were discharged home (P < .0001); 61% of patients with major stroke were discharged to a rehabilitation or skilled nursing facility. Patients with major stroke cost 4.4 times and 3.0 times that of patients with minor stroke in 2000 and 2005, respectively. Making up less than one third of all patients, patients with major stroke accounted for 60% of the total in-hospital cost of acute stroke care.CONCLUSIONS: BASIS, a neuroimaging-based stroke classification system, is highly effective at predicting in-hospital resource use, acute-hospitalization cost, and outcome. Predictive ability was maintained across the years studied.